(−)‐Epigallocatechin‐3‐Gallate Ameliorates Photodynamic Therapy Responses in an In Vitro T Lymphocyte Model. (3rd April 2014) - Qi, Hang; Abe, Naomi; Zhu, Beiwei; Murata, Yoshiyuki; Nakamura, Yoshimasa
<x xml:space="preserve">Abstract</x> (−)‐Epigallocatechin‐3‐gallate (EGCG), the most abundant polyphenolic constituent in green tea, is known as a powerful antioxidant but concomitantly possesses a prooxidant property. We investigated the effect of EGCG on phloxine B (PhB)‐induced photocytotoxicity in human T lymphocytic leukemia Jurkat cells. EGCG significantly potentiated PhB‐induced photocytotoxic effects, including the inhibition of cell proliferation, DNA fragmentation, and caspase‐3 activity induction in Jurkat cells. Catalase attenuated the enhanced cytotoxicity by EGCG, suggesting the involvement of extracellularly produced hydrogen peroxide. Indeed, EGCG significantly enhanced extracellular hydrogen peroxide formation induced by photo‐irradiated PhB. The EGCG also enhanced intracellular reactive oxygen species accumulation, c‐Jun N‐terminal kinase (JNK) phosphorylation, and interferon‐γ (IFN‐γ) gene expression, all of which are involved in PhB‐induced apoptosis. Taken together, our data suggest that EGCG is capable of potentiating photodynamic therapy responses, presumably through the intracellular oxidative stress‐sensitive JNK/IFN‐γ pathway by exogenous hydrogen peroxide formation. Copyright © 2014 John Wiley & Sons, Ltd.